2017
DOI: 10.1080/10790268.2017.1372058
|View full text |Cite
|
Sign up to set email alerts
|

Creatine or vitamin D supplementation in individuals with a spinal cord injury undergoing resistance training: A double-blinded, randomized pilot trial

Abstract: Supplementation with creatine may improve muscle strength parameters in individuals with spinal cord injury. Vitamin D deficiency is highly prevalent in this population. It is recommended an initial screening of vitamin D levels at the beginning of the physical rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…In subjects with spinal cord injury, Cr levels improve muscle strength parameters, and this has a positive effect on the performance of daily activities and body health [37]. In Paralympic weightlifting athletes, who have suffered spinal cord injury, creatine can help to maximize the performance of the upper limbs by reducing the FI and providing a faster recovery during the practices provided by the sport [38].…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with spinal cord injury, Cr levels improve muscle strength parameters, and this has a positive effect on the performance of daily activities and body health [37]. In Paralympic weightlifting athletes, who have suffered spinal cord injury, creatine can help to maximize the performance of the upper limbs by reducing the FI and providing a faster recovery during the practices provided by the sport [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also evaluated the impact of creatine supplementation on mild traumatic brain injury (TBI) and spinal cord injury (SCI) outcomes in animals [ 3 , 6 , 171 , 262 , 263 , 264 , 265 , 266 ]. For example, Sullivan and coworkers [ 264 ] found that provision of creatine in the diet for 5 days prior to TBI decreased the amount of cortical brain damage by 36% in rats and 50% in mice.…”
Section: Potential Therapeutic Role Of Creatine Supplementationmentioning
confidence: 99%
“…For example, Jacobs et al [ 268 ] reported that creatine supplementation (20 g/day for 7 days) enhanced aerobic exercise capacity and ventilatory anaerobic threshold in patients with cervical SCI. Moreover, Amorim et al [ 266 ] reported that individuals with SCI who consumed creatine (3 g/day for 8 weeks) with vitamin D (25,000 IU/day) while participating in a resistance-training program experienced significantly greater improvements in arm muscle area, strength, and functional capacity. While some studies report no benefit of creatine supplementation in patients with SCI [ 269 , 270 ], there is compelling evidence that creatine supplementation may reduce the severity of mild concussions, TBI, and/or SCI in animal models [ 21 , 263 ].…”
Section: Potential Therapeutic Role Of Creatine Supplementationmentioning
confidence: 99%
“…Supplementation with creatine to improve muscle strength in patients with chronic SCI has been also evaluated, with conflicting results. Two studies found no effect of creatine supplementation either on hand strength (78) or wheelchair performance (79), while two studies found some positive effects on upper extremity strength and function (80,81). All these diverse correlations highlight the need for a prompt and precise nutritional assessment in SCI patients, focusing on correct daily energy intake and a higher fiber and micronutrient intake (i.e., vitamin D and calcium).…”
Section: Nutritional Interventionsmentioning
confidence: 99%